BIOM-63. IDENTIFICATION OF MIRNA IN CEREBROSPINAL FLUID AND PLASMA AS A BIOMARKER TO SUPPORT MRI EVALUATION AND MONITORING OF PEDIATRIC BRAIN TUMORS. (14th November 2022) - Coyle, Anne; Familiar, Ariana; Zhao, Chao; Rathi, Komal; Hollawell, Madison; Choudhari, Namrata; Foster, Jessica; Naqvi, Ammar; Bagheri, Sina; Anderson, Hannah; Vidal, Lorenna; Vossough, Arastoo; et al.
Abstract: MRI is the current gold standard imaging technique for diagnostic evaluation and monitoring of pediatric CNS tumors, however MRI measures are unable to fully relate to tumor biology and molecular stratification. Circulating in blood and cerebrospinal fluid (CSF), miRNAs are an abundant and stable nucleic acid which can be utilized as a tumor biomarker. Relating miRNA biomarkers and radiological tumor measurements may provide improved diagnostic and monitoring tools for pediatric brain tumors. Using a cohort of 54 pediatric brain tumors including low grade glioma, ependymoma, germ cell tumor, medulloblastoma, atypical teratoid rhabdoid tumor and high-grade glioma we attempted to combine MRI findings and circulating miRNA data. The miRNA expression was profiled in 33 CSF and 52 plasma samples using the HTG EdgeSeq platform. Clinically acquired, multi-parametric MRI scans at time-points close in proximity to liquid biopsy collection were collected retrospectively and used to generate volumetric tumor segmentations. We identified unique miRNA targets significantly correlated with MRI features, clinical findings, and patient outcomes. In both CSF and plasma, miRNA expression was identified to correlate with diagnosis and clinical features including tumor grade and survival status (p < 0.05). In CSF, miRNA expression was correlated with MRI measurements including cystic core volume, non-enhancing tumor volume, leptomeningeal disease, tumor size and location (p < 0.05). Combination of miRNA targets and radiomic tumor measurements improved diagnostic predictions between low- and high-grade tumors. In plasma, miRNA expression was correlated with MRI measurements including cystic core volume, location, and leptomeningeal disease (p < 0.05). These results demonstrate utility of miRNAs as a pediatric brain tumor biomarker which combined with imaging features can improve minimally to non-invasive diagnostics and management of pediatric brain tumors.